Origin of mud in turbidites and hybrid event beds: Insight from ponded mudstone caps of the Castagnola turbidite system (north‐west Italy). Issue 5 (10th March 2020) - Patacci, Marco; Marini, Mattia; Felletti, Fabrizio; Di Giulio, Andrea; Setti, Massimo; McCaffrey, William
Abstract: The partitioning of different grain‐size classes in gravity flow deposits is one of the key characteristics used to infer depositional processes. Turbidites have relatively clean sandstones with most of their clay deposited as part of a mudstone cap or as a distal mudstone layer, whereas sand‐bearing debrites commonly comprise mixtures of sand grains and interstitial clay; hybrid event beds develop alternations of clean and dirty (clay‐rich) sandstones in varying proportions. Analysis of co‐genetic mudstone caps in terms of thickness and composition is a novel approach that can provide new insight into gravity flow depositional processes. Bed thickness data from the ponded Castagnola system show that turbidites contain more clay overall than do hybrid event beds. The Castagnola system is characterized by deposits of two very different petrographic types. Thanks to this duality, analyses of sandstone and mudstone composition allow inference of which proportion of the clay in each of the deposit types was acquired en route . In combination with standard sedimentological observations the new data allow insight into the likely characteristics of their parent flows. Clean turbidites were deposited by lower concentration, long duration, erosive, muddy turbidity currents which were more efficient at fractionating clay particles away from their basal layer. Hybrid event beds were deposited by shorter duration, higher‐concentration, less‐erosive sandier flows which were less efficient at clay fractionation. The results are consistent with data from other turbidite systems (for example, Marnoso‐arenacea). The approach represents a new method to infer the controls on the degree of clay partitioning in gravity flow deposits.